PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Widodo, Putry Meilinda Rahayu; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
One of the primary objectives of the company is to optimize the firm value. This research is meant to examine the influence of investment decision, funding decision, and the dividend policy to the Firm Value.The samples are 38 consumer goods companies which are listed in Indonesia Stock Exchange (IDX) during the 2010-2014 periods which is suitable with the determined criteria and 12 companies have been obtained as samples. This research has been done by using purposive sampling method. The data analysis has been applied in this research is done by using multiple linear regressions with the application instrument of SPSS (Statistical Product and Service Solutions).The result of the research shows that investment decision has significant influence to the firm value, funding decision does not have any significant influence to the firm value, and dividend policy has significant influence to the Firm Value. The value of R square is 0,333 which shows that all of independent variables which are investment decision, funding decision, and dividend policy can explain the dependent variable i.e. firm value is 33,3% and the remaining is 66,7% which is influenced by other factors which are not included in this model.Keywords: Investment Decision, Funding Decision, Dividend Policy, Firm Value.